Characterization of chronic renal disease in elderly adults - Julio César Candelaria-Brito; Carlos Gutiérrez-Gutiérrez; Héctor Demetrio Bayarre-Vea; Claudia Acosta -Cruz; Delia Margarita Montes de Oca; Orestes Labrador-Mazón (Asociación Colombiana de Nefrología e Hipertensión Arterial, 2018)
Introduction: chronic kidney disease generates numerous health expenses and is highly prevalent elderly.Objective: to characterize elderly patients with chronic kidney diseaseresident in the Consolación del Sur municipality, from May 2014 to September 2014. Methodological design: observational, descriptive and cross-sectional study, in the Doctor's and Family Nurse's offices 13, 14 and 42 in the Popular Council of Drivers Connection. The universe was of 389 patients and the sample of 109, fulfilling the inclusion criteria. The following variables were analyzed: age, sex, skin color, schooling, socioeconomic status, classification of chronic kidney disease and family and social support networks. The abbreviated MDRD formula was used to determine the degree of chronic kidney disease. To make an exit, descriptive statistics were used (absolute and relative frequencies, X2 test for Regression, X2 Bartholomeus). Informed consent was taken into account. Results: stage 2 prevails, with 51 patients (46.8%) and whites 82 (75.2%), in the 70-79 age group, 56.9% belonged, there was a predominance of men with 71 (65.1%). 63.3% have barely reached the primary level or did not finish it. There was a predominance of a low socioeconomic level (68.8%) and most had support networks (96, for 8 8.1%). Conclusions: the characterization of the chronic kidney disease from the sociodemographic approach has an important role in the integral approach of the disease in the primary level of health.